Learning process for life skills development of misstepping children and juveniles - เชาวตะ กรรฑิมา; พิพัฒน์เพ็ญ มณฑนา; ธรรมสัจการ วันชัย (Journal of Liberal Arts Prince of Songkla University, 2016)
This article focuses on the learning process for life-skill development of misstepping children and juveniles at the Children and Juvenile Training Center so as to help them return to live happily with other people with dignity and self-value. The study was conducted using the narrative approach based on the social constructivism paradigm emphasizing learning through talking and exchanging life experience between officers of the Regional Juvenile Vocational Training Centre (9), Songkhla Province and 17 juveniles who attended the training. The data were collected during Jauary-April 2011. The results of the study revealed that life skill development of the misstepping children and juveniles did not take place only because they had been through the life skill development process similar to the learning and teaching process of other schools in general where the focus was on development of the cognitive and psychomotor domains through vocational training and non-formal education. These children and juveniles had been through the process of learning about the world, society, other people, and their own selves, especially the therapeutic process focusing on understanding oneself. Having opportunity to check their own life history and know the negative identities given to them by society makes them realize and understand themselves well enough to know the main social discourse, and to build new knowledge in order to enable themselves to return to live in the society with dignity once again.